Staffing Policy by Educational Leaders: Reflection of The Values of Surah Al-Fatihah in Determining The Quality of Educational Human Resources - Raudah, Nanda Zahratu; Thohri, Muhammad (Jurnal Ilmiah Profesi Pendidikan, 2025)
Staffing policy by educational leaders plays a crucial role in determining the quality of educational human resources, which directly impacts the learning process and educational success. This study aims to examine how the values contained in Surah Al-Fatihah are reflected in the staffing policies adopted by educational leaders to improve the quality of educational human resources. This research uses a qualitative approach with a case study method in several educational institutions. Data were collected through in-depth interviews with school principals, teachers, and observations of staffing practices in various schools. Data analysis was conducted using a thematic approach to explore the connection between the values of Surah Al-Fatihah, such as guidance towards the straight path, justice, and balance in staffing policies. The results indicate that educational leaders who apply the principles found in Surah Al-Fatihah are able to create an educational environment that is fair, transparent, and focused on the development of high-quality human resources. In conclusion, staffing policies based on the values of Surah Al-Fatihah can enhance the quality of education through the selection and development of competent educators. The implications of this study highlight the importance of integrating spiritual values in educational policy decision-making.